Response of Cayenne Pepper Plants (Capsicum frutescens L.) to Application of Liquid Organic Fertilizer from Coconut Water Waste (Cocos nucifera L.) and Pineapple Peel (Ananas comosus L. Merr.) on Peat Soil - Feni Wulandari; Riza Linda; Irwan Lovadi (Jurnal Biologi Tropis, 2023)
Cayenne pepper (Capsicum frutescens L.) is one of the horticultural commodities that has high economic value and market demand. Cayenne pepper production in West Kalimantan is low due to soil conditions dominated by peatlands with high acidity and low soil fertility. Resetting soil fertility can be done using liquid organic fertilizers (LOF) such as coconut water waste and pineapple peel. Both types of LOF have nutrient values that are sufficiently beneficial for plants. This study aims to determine the response of cayenne pepper plants to applying both types of liquid organic fertilizer (LOF) alone and the effect of the combination of liquid organic fertilizer of coconut water waste and pineapple peel. This study uses a completely randomized design (CRD) with a factorial pattern consisting of 2 factors, namely coconut water waste and pineapple peel waste liquid organic fertilizer. Each factor consists of 4 treatment levels and is repeated 4 times, namely A (coconut water POC) A0 = 0 ml (control); A1 = 150 ml; A2 = 250 ml; A3 = 350 ml; B (pineapple peel POC) B0 = 0 ml (control); B1 = 50 ml; B2 = 100 ml; B3 = 150 ml. Data were analyzed using the Analysis of Variance (ANOVA) test and continued with the Tukey test at the 5% test level. The results showed that the treatment of  350 mL coconut water POC / 150 mL pineapple peel POC in combination gave a significantly different effect on height, number of branches, flowering time, number of flowers, number of fruits, wet weight and dry weight of plants.